GAMBARAN PENGETAHUAN SISWA TENTANG PERILAKU SEKS BEBAS DI SMA/SMK KOTA LUBUKLINGGAU TAHUN 2016 - Rini Mayasari Rini Mayasari (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2016)
ABSTRACT Free sex is a relationship that is done by men and women without matrimony. Various forms of sexual behavior, such as intimate dating, courtship, to have sexual contact. Factors associated with sex behavior among others, is the lack of knowledge about free sex, free sex impact, forms of promiscuity, perversion LGBT, and disease-free sex. This study design is the technique of sampling using quantitative indirectly using a questionnaire tools shaped questionnaires. Be knew overview of students' knowledge about sex in high school / vocational Lubuk Linggau Year 2016. The study population was high school class XII students in schools in the city Lubuklingga 2016. The sample in this study is the high school class XII students in 9 schools there in Lubuklinggau of 167 people. Results of univariate analysis showed respondent knowledge about free sex amounted to 48 people (28,74%), students with sufficient knowledge of 54 people (32,33%), and students with less knowledge of 65 people (38, 93%). Students with a good knowledge about the impact of free sex amounted to 57 (34,13%), students with sufficient knowledge of 69 people (41,31%), and students with less knowledge 41 (24,56%). Students with a good knowledge about the form of free sex amounted to 58 students (34,73%), students with sufficient knowledge totaled 49 peoples (29,34%), and students with less knowledge of 60 people (35,93%). Students with a good knowledge about LGBT amounted to 54 (32,34%), students with sufficient knowledge amounted to 68 peoples (40.71%), and students with less knowledge amounted 45 peoples (26,95%). Students with a good knowledge about the disease free sex amounted to 22 peoples (13,17%), students with sufficient knowledge of 39 peoples (23,35%), and students with less knowledge amounted to 106 peoples (63,48%). ABSTRAK Seks bebas merupakan hubungan yang dilakukan oleh laki-laki dan perempuan tanpa adanya ikatan perkawinan. Berbagai bentuk tingkah laku seksual, seperti berkencan intim, bercumbu, sampai melakukan kontak seksual. Faktor-faktor yang berhubungan dengan perilaku seks bebas antara lain adalah kurangnya pengetahuan tentang seks bebas, dampak seks bebas, bentuk-bentuk seks bebas, penyimpangan LGBT, dan penyakit seks bebas. Desain penelitian ini adalah teknik pengambilan sampel menggunakan teknik kuantitatif yaitu secara tidak langsung menggunakan alat bantu angket berbentuk kuisener. Di ketahuinya gambaran pengetahuan siswa tentang seks bebas di SMA/SMK Kota Lubuk Linggau Tahun 2016. Populasi penelitian ini adalah siswa kelas XII SMA di sekolah yang ada di Kota Lubuklingga tahun 2016. Sampel pada penelitian ini adalah siswa kelas XII SMA di 9 sekolah yang ada di Kota Lubuklinggau yang berjumlah 167 orang. Hasil analisis univariat menunjukan respondent pengetahuan tentang seks bebas berjumlah 48 orang (28,74%), siswa dengan pengetahuan cukup 54 orang (32,33%), dan siswa dengan pengetahuan kurang 65 orang (38,93%). Siswa dengan pengetahuan baik tentang dampak perilaku seks bebas berjumlah 57 orang (34,13%), siswa dengan pengetahuan cukup 69 orang (41,31%), dan siswa dengan pengetahuan kurang 41 orang (24, 56%). Siswa dengan pengetahuan baik tentang bentuk perilaku seks bebas berjumlah 58 siswa (34,73%), siswa dengan pengetahuan cukup berjumlah 49orang (29,34%), dan siswa dengan pengetahuan kurang berjumlah 60 orang (35,93%). Siswa dengan pengetahuan baik tentang LGBT berjumlah 54 orang (32,34%), siswa dengan pengetahuan cukup berjumlah 68 orang (40,71%), dan siswa dengan pengetahuan kurang berjumlah 45orang (26,95%). Siswa dengan pengetahuan baik tentang penyakit seks bebas berjumlah 22 orang (13,17%), siswa dengan pengetahuan cukup 39 orang (23,35%), dan siswa dengan pengetahuan kurang berjumlah 106 orang (63,48%).